Case report: A case report and literature review of extrapancreatic solid pseudopapillary neoplasm - Liu, Hang; Xu, Zhiquan; Wang, Yaxu; Gu, Haitao; Tang, Yunhao; Wu, Dabin; Wang, Jijian; Zhang, Jianbo (Frontiers in Surgery, 2022)
Background: Solid pseudopapillary neoplasm (SPN) is a rare tumor of low malignant potential that typically occurs in the pancreas. Extrapancreatic SPN is also extremely rare worldwide. Case presentation: We report a 70-year-old woman hospitalized with abdominal pain and bloating. The patient did not have any underlying diseases, such as diabetes, coronary heart disease, or hypertension. More than 30 years ago, the patient underwent surgery for "ectopic pregnancy". The patient had no family history of hereditary disease, nor did any immediate family members have a history of cancer. Laboratory tests showed that her hemoglobin and albumin were decreased and she had elevated cancer antigen 125 (CA125). Enhanced computed tomography (CT) showed a large tumor in the abdomen and pelvis. The patient subsequently underwent surgery, during which it was found that the tumor was attached to the terminal ileum. Pathological findings suggested that the tumor was an extrapancreatic SPN, and an ectopic pancreas was found in the tumor tissue. The patient did not receive chemotherapy or radiotherapy after surgery. After thirteen months of follow-up, the patient was admitted again with abdominal pain. CT showed tumor recurrence with extensive systemic metastases. The patient and her family refused reoperation and biopsy, and the patient was discharged after the abdominal pain and anemia resolved. Conclusion: We report a rare case of extrapancreatic SPN of ileal origin, which could be the first report worldwide. It had aggressive biological features, with recurrence and metastasis thirteen months after surgery. For extrapancreatic SPN, the risk of recurrence should be assessed, and for tumors suspected of malignant behavior, a longer follow-up after discharge may be needed. Although SPN generally has a good prognosis after surgery, there is no consensus on whether postoperative chemotherapy and other treatments are needed for patients with a high recurrence risk.